Spin Hall magnetoresistance in the non-collinear ferrimagnet GdIG close to the compensation temperature - Dong, Bo-Wen; Cramer, Joel; Ganzhorn, Kathrin; Yuan, H. Y.; Guo, Er-Jia; Goennenwein, Sebastian T. B.; Klauei, Mathias (Journal of Physics: Condensed Matter, 2018)
We investigate the spin Hall magnetoresistance (SMR) in a gadolinium iron garnet (GdIG)/platinum (Pt) heterostructure by angular dependent magnetoresistance measurements. The magnetic structure of the ferromagnetic insulator GdIG is non-collinear near the compensation temperature, while it is collinear far from the compensation temperature. In the collinear regime, the SMR signal in GdIG is consistent with the usual sin2θ relation well established in the collinear magnet yttrium iron garnet, with θ the angle between magnetization and spin Hall spin polarization direction. In the non-collinear regime, both an SMR signal with inverted sign and a more complex angular dependence with four maxima are observed within one sweep cycle. The number of maxima as well as the relative strength of different maxima depend strongly on temperature and field strength. Our results evidence a complex SMR behavior in the non-collinear magnetic regime that goes beyond the conventional formalism developed for collinear magnetic structures.
CRIS-Team Scopus Importer:2023-03-27
Keywords: non-collinear ferrimagnet; spin current; spin Hall magnetoresistance